Electrochemical biosensors for cytokine measurement : the first electrochemical biosensor based on the natural receptor of the Interleukine-5 (2025)
Cytokines are proteins that regulate the immune system, increasing or decreasing according to the immunophysiological state. Although measuring cytokines can have diagnostic value, their levels are often variable and complex to analyze given their pleiotropism, their essentially paracrine activity, and the synergy between them and other immune mediators. Additionally, cytokines are produced and destroyed immediately after the sample is taken, posing a clear challenge for their monitoring as biomarkers in the health-disease process. In this context, developing highly specific and sensitive devices for cytokines monitoring is required. Electrochemical biosensors could be an alternative to conventional techniques for determining cytokines. Given the possibilities of miniaturization, low costs, and remarkable metrological virtues, electrochemical biosensors have been proposed for point-of-care testing (POCT) and permanent monitoring in wearable devices. The latter are the two best technological approaches to avoid the aforementioned problems in cytokine measurement. Since natural cytokine receptors have a single ligand, their specificity and selectivity are among the highest found in nature. Here, the possibility of using natural cytokine receptors as bioreceptors to assemble electrochemical biosensors for their measurement is explored as a working hypothesis. Then, the general objective was to develop an electrochemical biosensor for measuring interleukin-5 using the alpha chain of its natural receptor (IL-5Rα) as a bioreceptor. The methodological approach included a systematic review of the biology involved in the biodistribution and general mechanism of action of cytokines (and other analytes with similar behavior). The leading electrochemical platforms used for cytokine monitoring were also contrasted in POCT and wearable formats (i.e., real-time or continuous). Both IL-5 and a recombinant form of IL-5Rα with a poly-glycine and poly-histidine tag (Gly-His IL-5Rα) were refolded from inclusion bodies isolated from Escherichia coli. IL-5-based affinity chromatography and infrared analysis suggested adequate refolding. Gly-His IL-5Rα was immobilized on a carbon working electrode electroplated with nickel oxide nanoparticles. Electrochemical and X-ray spectroscopic (XPS) analyses confirmed the surface functionalization of the electrode. An impedimetric platform capable of detecting IL-5 in phosphate buffer spiked with serum was assembled. The dynamic linear range was 0.125-2.5 µg/mL, and the detection limit was 150 ng/mL. To our knowledge, this is the first published electrochemical biosensor using IL-5Rα as a bioreceptor, highlighting the novelty of the work and the contribution to the state-of-the-art. It suggests that it is possible to employ natural cytokine receptors as bioreceptors to improve the specificity and selectivity of electrochemical biosensors and extend their use to study protein-protein interactions. From this perspective, further work is required to produce more stable and scalable natural receptors and more efficient immobilization strategies.